Analysis of Urea Pyrolysis Products in 132.5-190 °C. (February 2019) - Wang, Denghui; Dong, Ning; Hui, Shien; Niu, Yanqing
Abstract: In this thesis, the urea pyrolysis process in the temperature range from 132.5 °C to 190 °C was studied by a self-built fixed bed experimental system, in order to explore the distribution properties of urea pyrolysis products and the rule of occurrence of dominant reaction in the temperature range from 132.5 °C to 190 °C.